Many Meats and Many Milks? The Ontological Politics of a Proposed Post-animal Revolution. (2nd January 2019) - Jönsson, Erik; Linné, Tobias; McCrow-Young, Ally
ABSTRACT: Today plant-based alternatives to animal-agricultural products are made available or developed alongside 'cultured' meat, and products utilising genetic modification. To proponents, this signifies the emergence of 'cellular agriculture' as a food-production field or the possibility of a 'post-animal bioeconomy': a way to safely and sustainably produce animal products without animals. Drawing on previous work on ontological politics enables acknowledging how these novel objects unsettle animal products' ontological stability, thereby offering a practical case of how the world is multiply produced. An important emphasis within this tradition is the situated nature of reality-making practices. Consequently our analysis, focusing on different practices, sites and objects compared to influential studies of ontological politics, necessitates bringing in hitherto relatively unexplored political-economic relations and legal processes. As global processes and problem formulations, laboratories, and national or regional regulations come together to remake realities the ontological-political dynamics determining the fate of cellular agriculture or a post-animal bioeconomy becomes shaped by a combination of conflicts and budding collaborations between proponents of new technologies and established livestock interests. Understanding these dynamics requires tracing both how post-animal products reshape the world they are introduced into, and acknowledging the friction evident as reality-carrying objects leave their laboratories.